Simulation and Analysis of the Elliptical Gear Used in Rack Type Pumping Unit - Tian Zhenzhen; Peng Yong; Zhang Haokun (Jixie chuandong)
According to the geometric characteristics of the elliptical gear,with different eccentricity ratio of ellipse,the different transmission ratio curve is got,and then the variable speed motion of pumping unit is completed. By using the Solid Works,the 3D modeling and motion simulation of the pumping unit are completed,and by using MATLAB,the digital simulation of the elliptical gear pumping unit is completed. Comparing with the suspension point velocity and acceleration between the ordinary pumping unit and the elliptical gear pumping unit,it is finally verified that the motion performance of the pumping unit is improved by using elliptical gear to the pumping unit,which reduces the vibration impact and the energy consumption.